Ізотерми гiдратацiї чистих та мiнералiзованих колагенових фiбрил: дослiдження з використанням п’єзогравiметрiї та iнфрачервоної спектроскопiї - Суходуб, Л.Б.; Самченко, Ю.М.; Суходуб, Л.Ф. (Видавничий дім "Академперіодика" НАН України, 2008)
Influence of the mineralization of collagen fibrils on their hydration in vitro is considered using piezogravimetric and infrared data. A model illustrating the mineralization process with the consideration of two specific water structures is proposed to explain the obtained hydration isotherms.